Discussion sur ie facteur de concentration du 32P dans enteromorpha linza de la mer noire litoral roumain - Șerbănescu, O. (Cercetări Marine - Recherches Marines, 2026)
The author analyzed the variation of the accumulation rate of 32P in Enteromorpha Linza under variable salinity conditions and evaluated the ranges within which this ratio assumed normal values. Concomitantly, the saline composition of the vegetal fluid was determined by the deep freezing point method; this explained the physiological disturbances in the plant, having a direct effect on the radionuclides accumulation